A structural analysis of twenty Maguindanaon folktales. - Estorque, Christine May Perion (2009.)
The study sought to find out the following: 1) the similitude in structure among the twenty folktales using Joseph Campbell's Monomyth; and 2) the parallelism among the monomyths of the twenty folktales. This study utilized a structuralist approach particularly focusing on Joseph Campbell's concept of Monomyth with Claude Levi-Strauss' Structural Study of Myth as foundation of structural analysis but only twenty from the forty six tales from the book Maguindanaon Folktales were used. The study revealed that the folktales of the Maguindanaons share similar categories and quite a number of stages in Monomyth. It appeared that the Maguindanaon structure doesn't have the Refusal to the Call, Refusal to the Return, the Magic Flight and Rescue from without stages. It revealed that the Maguindanaon Folktales have deviated from the standards of Monomyth - the fundamental structure of the narratives around the world according to Campbell. In addition, the Maguindanaon males have stronger heroic tendencies unlike the heroes of the western mythology. Moreover, the Maguindanaon stories are inspired by Islamic culture and tradition.
Thesis (Undergraduate, Bachelor of Arts in Literature-Broadcast Communication) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Folktales -- Maguindanaon